Modelo de Insumo-Produto Dinâmico: Construção, Solução e Estabilidade - Tácito Augusto Farias; Nehemias Anastácio Santos da Silva (Revista de Economia Mackenzie, 2009)
In this article have been developed a time continuous dynamic input-output model that shows the development of products, two industries over time. We did our paper, first building a abstract model of two specific sectors, then use a numerical example consistent. We also present our version of the model system of quantities and prices and apply the Stability Dual theorem showing that as one of the systems is stable, the other will be stable (hence occure the duality).